STRATEGI BERTAHAN HIDUP PARA NELAYAN DI WILAYAH PERBATASAN BATAM-SINGAPURA - Muhammad Fadli; Siti Arieta; Sri Wahyuni (JURNAL SOSIO-KOMUNIKA, 2023)
The fishermen in Pemping Village, Rear Padang District, Batam City, are poverty-stricken in terms of fulfilling basic needs for the dynamics that occur in the eyes, causing the search for fish to be not optimal and not getting high selling prices for fish. In addition to poverty affecting fishermen caused by educational background, fishing that is not optimal, and not getting high selling prices, fishermen from the Pemping Village are also faced with problems with illegal smuggling activities. Furthermore, the Pemping community faces restricted access to fishing areas. International fishing transactions to Singapore, due to the increasing stringency of regulations by the two countries, requires the form of a strategy to meet the daily needs of fishing families. The method used in this research is a qualitative research method with a descriptive approach. The theory used is French Fukuyama's social capital as an analytical knife in this study. The results of this study are the trust of fellow fishermen gaining trust in the form of work, lending, and borrowing money. The two values and norms that are applied in society include maintaining friendship, helping each other, and feeling the same fate. The three social networks that exist among fishermen, relatives, and neighbors are used to obtain information on potential fish stocks and job vacancies, as well as obtain information on access to selling to middlemen at higher prices. Other strategies are adding working hours, looking for side jobs, and taking advantage of the potential of families in every house holds including women in fulfilling family needs.